UTILIZATION OF CANANA AS A MEDICINE IN LEGAL PERSPECTIVE IN INDONESIA - Ningtias, Ayu Dian; Risano, Alfredo; Hariati, Wida (Universitas Islam Lamongan, 2022)
Abstract The main problem in this research is that there is a conflict in Article 7 and Article 8. Where Article 8 Prohibition of the Use of Narcotics Group 1 for the Purpose of Health Services, while in Article 7 Narcotics can be used for the benefit of health services. Articles in the Narcotics Law currently conflict with other articles, causing many interpretations and legal uncertainty in the enforcement of the use of cannabis plants as medicine in society. The Use of Cannabis as a Drug Perspective of Indonesian Criminal Law and Islamic Law. It can be concluded in the Indonesian Criminal Law research on the Use of Cannabis as a Drug, currently many articles related to Narcotics are still in conflict with other articles, causing uncertainty in the law against the use of marijuana as a drug. The state must be able to codify the Law on Narcotics, so that these articles do not conflict with other articles, and so that there are no more losses experienced by the community and the state in the war on drugs. Whereas in Islamic Criminal Law it refers to the Qur'an and Hadith as well as the ijtihad of scholars. Cannabis plants can be used as long as it is intended for medicinal purposes, and provides punishment in the form of ta'zir against all forms of abuse. Whereas in ijtihad scholars through the qiyas method which equates cannabis plants with khamr, it does not meet the qiyas element, where in equating it with khamr which is clearly different in terms of content, substance, or the resulting effect. So that qiyas equating marijuana with khamr cannot determine the prohibition of cannabis plants as medicine. Whereas in the maslahah al-mursalah method, as long as the use of marijuana as a drug is regulated in its use so that it gets benefits, the use of marijuana as a halal drug is used, because it is already a rule of use as a drug against experts.